Kebebasan Ekspresi vs Norma Keluarga: Negosiasi Etika Berbusana antara Remaja dan Orang Tua di Era Postmodern - Trisnani Widowati; Anik Maghfiroh; Nathania Citta Pribawanto; Elina Sudi Dwi Ariyani; Zakiyya Dewi Salsabila; Raisa Marchella Maulida; Vanesa Monica (Pusat Riset dan Inovasi Nasional, 2025)
The development of postmodern culture has had a major influence on the way teenagers express their identity through clothing. Dress style is no longer just a matter of aesthetics, but has also become a symbol of freedom of expression that often clashes with family norms that uphold moral, religious, and cultural values. This study aims to understand the dynamics of fashion ethics negotiation between teenagers and parents in the postmodern era through an analysis of social, cultural, and family communication perspectives. The study uses a qualitative method with a literature review approach of 15 national journals discussing the role of parents, freedom of expression, fashion ethics, and the influence of global culture on teenagers. The results show that value negotiation occurs through open communication between parents and children, where both parties try to adjust moral values to the needs of self-actualization. Parents act as moral guides, while adolescents seek to obtain freedom that is still in line with social norms. This study contributes to the strengthening of character education, family communication patterns, and strategies for instilling ethical dress values amid the challenges of modern culture.